The works and background of Luis Barragan - Yamazaki, Yasutaka (A+U)
Se compilan obras de Luis Barragan. Contiene: House & Atelier, Tacubaya, México, 1947. House for Gilardi, Tacubaya, México City, 1976- . Capel for the Capuchinas Sacramentarias del Purismo Corazon de Maria, Tlalpan, México, 1952-1955. Los Clubes, Suburbs of México City, 1963-1964. Towers of Satellite City, 1957 and Las Arboledas, 1958-1961, México City.